(untitled) (Journal of Computational Mathematics, 1990)
We present a semi-coarsening procedure, i.e., coarsening in one space direction, to improve the convergence rate of the multigrid solver presented in [5] for solving the 2D steady Navier-Stokes in primitive variables when the aspect ratio of grid cells is not equal to 1, i.e., when h_x/h_y 1 or 1, where h_x is the grid step in x direction and h_y is the grid step in y direction, x and y represent the Cartesian coordinates.